Exploring and expanding the Fe-terephthalate metal–organic framework phase space by coordination and oxidation modulation. Issue 12 (19th October 2021) - Bara, Dominic; Meekel, Emily G.; Pakamorė, Ignas; Wilson, Claire; Ling, Sanliang; Forgan, Ross S.
Abstract : Modulated self-assembly of Fe-terephthalate metal–organic frameworks allows fine control over phase formation, offers insight into kinetic and thermodynamic landscapes, and the discovery of novel materials in an already well-studied complex system. Abstract : The synthesis of phase pure metal–organic frameworks (MOFs) – network solids of metal clusters connected by organic linkers – is often complicated by the possibility of forming multiple diverse phases from one metal–ligand combination. For example, there are at least six Fe-terephthalate MOFs reported to date, with many examples in the literature of erroneous assignment of phase based on diffraction data alone. Herein, we show that modulated self-assembly can be used to influence the kinetics of self-assembly of Fe-terephthalate MOFs. We comprehensively assess the effect of addition of both coordinating modulators and pH modulators on the outcome of syntheses, as well as probing the influence of the oxidation state of the Fe precursor (oxidation modulation) and the role of the counteranion on the phase(s) formed. In doing so, we shed light on the thermodynamic landscape of this phase system, uncover mechanistics of modulation, provide robust routes to phase pure materials, often as single crystals, and introduce two new Fe-terephthalate MOFs to an already complex system. The results highlight the potential of modulated self-assembly to bring precision control and new structural diversity to systems that have already received significant study.